Indonesian State Intelligence Agency’s Responsibility in Negligence Wiretapping Evidence of Terrorism Suspect - Aryasepta Syaelendra; Frans Simangunsong (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Wiretapping evidence include in confidential evidence which need to be guarded and become State Intelligence needs for prove at trail court purpose, this become crutial to keep in mind this confidential evidence is State Intelligence’s responsibility to keep convidential secret. negligence nor deliberate State Intelligence personel in keeping wiretapping evidence that usually form as voice convertation record or personal text massages from suspects and/or terorism executant becomes important when it comes to confidential guarantee remembering it writtens on Undang – undang, proofing convidential evidence on court are needs to prove for the purpose of next investigation. State Intelligence can get permission doing wiretapping for the next six month untill undetermined time limit, Lack of laws in which regulates specifically regarding the responsibilities of the Intelligence Agency if negligence occurs in preserving evidence becomes important and not limited to code of ethics sanctions. Using normative juridical methods to find out the basic basis for the importance of updating the Intelligence Agency's code of ethics in accounting for the evidence carried by each personnel. Apart from that, this research also aims to determine the form of accountability of the State Intelligence Agency in its responsibilities.